Relationship between Locations of Rib Defects and Loss of Respiratory Function—A Biomechanical Study - Hatano, Asako; Nagasao, Tomohisa; Cho, Yasunori; Shimizu, Yusuke; Takano, Naoki; Kaneko, Tsuyoshi; Kishi, Kazuo (The Thoracic and Cardiovascular Surgeon, 2014)
Objective The present study elucidates the relationship between the locations of rib defects and loss of respiratory function.Methods Ten sets of three-dimensional finite element models were produced from computed tomography data of 10 persons and categorized as normal type models. These models were modified by removing part of the ribs, and the resultant models were categorized as defect type models. Varying the location of the defects, six types of defect model were produced from each of the 10 normal models; the defects were made on the anterior-superior, anterior-inferior, lateral-superior, lateral-inferior, posterior-superior, and posterior-inferior regions of the thorax. To simulate respiration, contracture forces were applied to nonlinear springs modeling respiratory muscles for each of the normal and defect models. Difference in volume of the thoracic cavity between inspiration and expiration phases was viewed as the indicator of respiratory function and was defined as ΔV. The values of ΔV were compared between normal type models and their corresponding defect type models.Results Among the six types of defect, the degree of functional loss was greatest with those defects on the lateral-inferior part of the thorax, where ΔV of the affected side hemithorax drops to 38 to 45% of normal values, whereas ΔV was 62 to 88% with other defect models.Conclusion Thoraces that have defects on their lateral-inferior regions present lower respiratory functioning than thoraces with other defect locations. Hence, in treating clinical cases where defects are expected to occur in this region, effort should be made to minimize the area of the defect.
Keywords: experimental; imaging (all modalities); physiology; pulmonary function; robotics